Quantification of Carbohydrates in Grape Tissues Using Capillary Zone Electrophoresis - Zhao, Lu; Chanon, Ann M.; Chattopadhyay, Nabanita; Dami, Imed E.; Blakeslee, Joshua J. (Frontiers in Plant Science, 2016)
Soluble sugars play an important role in freezing tolerance in both herbaceous and woody plants, functioning in both the reduction of freezing-induced dehydration and the cryoprotection of cellular constituents. The quantification of soluble sugars in plant tissues is, therefore, essential in understanding freezing tolerance. While a number of analytical techniques and methods have been used to quantify sugars, most of these are expensive and time-consuming due to complex sample preparation procedures which require the derivatization of the carbohydrates being analyzed. Analysis of soluble sugars using capillary zone electrophoresis (CZE) under alkaline conditions with direct UV detection has previously been used to quantify simple sugars in fruit juices. However, it was unclear whether CZE-based methods could be successfully used to quantify the broader range of sugars present in complex plant extracts. Here we present the development of an optimized capillary zone electrophoresis method capable of separating and quantifying mono-, di-, and tri-saccharides isolated from plant tissues. This optimized CZE method employs a column electrolyte buffer containing 130 mM NaOH, pH 13.0, creating a current of 185 µA when a separation voltage of 10 kV is employed. The optimized CZE method provides limits-of-detection (an average of 1.5 ng/µL) for individual carbohydrates comparable or superior to those obtained using gas chromatography-mass spectrometry, and allows resolution of non-structural sugars and cell wall components (structural sugars). The optimized CZE method was successfully used to quantify sugars from grape leaves and buds, and is a robust tool for the quantification of plant sugars found in vegetative and woody tissues. The increased analytical efficiency of this CZE method makes it ideal for use in high-throughput metabolomics studies designed to quantify plant sugars.